2017
DOI: 10.1186/s13046-017-0544-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin (mTORC1 inhibitor) reduces the production of lactate and 2-hydroxyglutarate oncometabolites in IDH1 mutant fibrosarcoma cells

Abstract: BackgroundMultiple studies concluded that oncometabolites (e.g. D-2-hydroxyglutarate (2-HG) related to mutant isocitrate dehydrogenase 1/2 (IDH1/2) and lactate) have tumour promoting potential. Regulatory mechanisms implicated in the maintenance of oncometabolite production have great interest. mTOR (mammalian target of rapamycin) orchestrates different pathways, influences cellular growth and metabolism. Considering hyperactivation of mTOR in several malignancies, the question has been addressed whether mTOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…In other study it was shown that rapamycin reduced 2-HG levels derived of lactate, in IDH1 mutant fibrosarcoma cell line (HT-1080 cells). Furthermore, they shown that rapamycin inhibit the growth in HT-1080 xenografts in vivo and 2HG production (188). In support with this, using two mutant cell lines for IDH and orthotopic mutant IDH tumor model, showed that the treatment with dual PI3K/mTOR inhibitor (XL765), induced a significant reduction in 2HG levels, and enhanced the survival (189).…”
Section: Hg and Mtorc1mentioning
confidence: 81%
“…In other study it was shown that rapamycin reduced 2-HG levels derived of lactate, in IDH1 mutant fibrosarcoma cell line (HT-1080 cells). Furthermore, they shown that rapamycin inhibit the growth in HT-1080 xenografts in vivo and 2HG production (188). In support with this, using two mutant cell lines for IDH and orthotopic mutant IDH tumor model, showed that the treatment with dual PI3K/mTOR inhibitor (XL765), induced a significant reduction in 2HG levels, and enhanced the survival (189).…”
Section: Hg and Mtorc1mentioning
confidence: 81%
“…The connection between glutaminolysis and glycolysis, their dependence on cellular mTOR activity [32] were deeply investigated in many previous glioma studies [31,33]. In addition, both mTOR complexes have been described to play an important role in the regulation of these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Intra- or extracellular metabolites - citrate, aKG, succinate, fumarate, malate, glutamate, 2-HG - were extracted by a modified method based on Szoboszlai et al [ 33 , 34 ]. Cells (minimum 5 × 10 5 cells) were quenched in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%